Transformation of NO in Combustion Gases by DC Corona - Oleksandr Molchanov; Kamil Krpec; Jiří Horák; Lenka Kuboňová; František Hopan; Jiří Ryšavý; Marcelina Bury (Fire)
This study investigates the performance of DC corona discharge electrostatic precipitators (ESPs) for NO conversion to increase DeNOx technologies’ efficiency for small-scale biomass combustion systems. Experiments were conducted using a 5 kW automatic wood pellet domestic heat source with combustion gas treated in a specially designed ESP operated in both positive and negative corona modes, resulting in a reduction in NO concentrations from 130 mg/m3 to 27/29 mg/m3 for positive/negative polarities (at 0 °C and 101.3 kPa). NO conversion efficiency was evaluated across a range of specific input energies (SIEs) from 0 to 50 J/L. The results demonstrate that DC corona ESPs can achieve up to 78% NO reduction, with positive corona demonstrating a greater energy efficiency, requiring a lower SIE (35 J/L) compared to the negative corona mode (48 J/L). A detailed analysis of reaction pathways revealed distinct conversion mechanisms between the two modes. In positive corona, dispersed active species distribution led to more uniform NO conversion, while negative corona exhibited concentrated reaction zones with about 20% higher ozone production. The reactions involving O and OH radicals were more important in positive corona, whereas ozone-mediated oxidation dominated in negative corona. The research results demonstrate that ESP technology with DC corona offers a promising, energy-efficient solution for NOx control in small-scale combustion systems.